Exploring the intention to buy Small and Medium Enterprise (SME) product among consumers in Melaka Tengah / Muhammad Zahid Sapian and Syuwadah Daud - Sapian, Muhammad Zahid; Daud, Syuwadah (Faculty of Business and Management, 2015)
This research paper is conducted to “explore the intention to buy Small and Medium Enterprises (SMEs) product among consumers in Melaka Tengah”. The objective of this study is to determine the level of intention to buy Small and Medium Enterprises (SMEs) product among consumer in Melaka Tengah and to examine the relationship between intention factors and the intention to buy Small and Medium Enterprises (SMEs) product among consumers in Melaka Tengah. In this study, the researcher had been distributed questionnaire to the 384 respondent were chosen by using simple random sampling. The SPSS was using to interpret the data for this study. The result shows that perceived cost, perceived quality, trust, and social influence have positive relationship between consumer intention buying. However, only trust has significant relationship between consumer intention buying. Meanwhile, the other independent variable did not have significant relationship with the dependent variable.